Peranan Komunikasi Keluarga Dalam Keberhasilan Belajar Siswa Sekolah Menengah Pertama di Kota Manado - Mingkid, Elfie ,; Londa, Very Y; Kalesaran, Edmond Royan (JURNAL ILMIAH SOCIETY, 2014)
Students in many learning activities are faced with learning difficulties, family economic problems, problems with school friends and adjustment problems with the applicable regulations. Required by her role and responsibility of parents to support the success of Siwa. This research using qualitative methods seek to reveal the phenomenon behind the role of family communication in the learning success of junior high school students in the city of Manado. From research conducted revealed that family communication that goes well show openness children to parents so that enhance the spirit of the child to learn and excel. However, family communications that do not go well make children have difficulty to deliver all the needs and problems encountered in the study. In such a situation makes the lack of support from parents in supporting children's learning achievement. Keywords: Family Communication, Success study, Students.